Application for Sexually Transmitted Infection Risk Assessment - Ajanović, Alen; Konda, Jaka; Fele-Žorž, Gašper; Gradišek, Anton; Gams, Matjaž; Peterlin, Ana; Počivavšek, Karolina; Matičič, Mojca (Informatica, 2017)
We present a web application to detect risks related to sexually transmitted infections (STIs). The application works as a questionnaire about sexual behaviour and risk factors for STIs and, based on the answers, calculates the risk of being infected. The application also works as an informational tool with educating about STI and prevention. It uses a combination of approaches from computer science and psychology to deliver a usable, clean interface with which the user feels safe.